Upaya Peningkatan Omzet Umkm Pada Masa Pasca Pandemi Covid-19 Melalui Kinerja Akuntan Dan Motivasi Usaha Di Kabupaten Banyumas - Aning Fitriana; Adhelia Desi Prawestri (Tirtayasa Ekonomika, 2021)
The purpose of this study was to analyze the performance of accountants and business motivation to increase turnover at MSMEs in Banyumas Regency. This study uses multiple linear regression analysis and SEM (Structural Equation Modeling). The results obtained indicate that the accountant's performance has a significant and positive effect on increasing turnover. Business motivation has a significant and positive influence on the increase in turnover and accountant performance as well as business motivation jointly influences the increase in turnover.